Assessing the Relationship Between Resilience, Humor Styles, and Retention Across Semesters - Staton, Tyler A; Tran, Justin H.; Osborne, Randall; Angulo, John; Johnson, Emma (Advances in Social Sciences Research Journal, 2025)
Humor styles have been connected to benefits and detriments to mood that are closely related to the trait of resilience. Furthermore, traits related to positive humor styles like mindfulness and openness to experience were linked to higher retention rates. The relationships between humor styles (affiliative, self-enhancing, aggressive, and self-defeating), resilience, and retention are largely understudied with mixed findings and limitations in methodology necessitating the need for further exploration. Using data from a sample of 405 university students, the study examines the predictive role of affiliative, self-enhancing, aggressive, and self-defeating humor styles on well-being through multiple regression analysis. Results indicate that affiliative and self-enhancing humor are positively associated with life satisfaction and positive affect, whereas aggressive and self-defeating humor are linked to increased negative affect. There was no association found between humor styles and retention. These findings underscore the complex role of humor in psychological well-being and suggest that retention may be influenced by other factors than humor styles.